Studi Potensi Limbah Debu Pengolahan Baja (Dry Dust Collector) sebagai Bahan Tambah pada Beton - Amalia Amalia (Jurnal Poli-Teknologi, 2011)
Abstract This research has the objectives of finding out the concrete properties, which are, workability, unit weight, compressive strength, flexural strength and finding out an optimum composition of dry dust collector waste in the concrete mixture. In this research, 3 different kinds of concrete mixture were created based on the amount of waste substitution in the concrete. The examined concrete mixture compositions were the concrete with water cement ratio = 0.68, with the waste substitution as much as 0%, 10%, and 20% of sand weight. The mechanical behavior of the concrete was tested at the age of 28 days.The research results show that, an addition of dry dust collector waste in the concrete influence concrete workability, unit weight of concrete with 10 % waste as much as 2497,44 kg/m3. The concrete with 10 % waste had the higher unit weight compare with the normal concrete without waste. The dry dust collector waste substitution as much as 10% in the concrete can improve compressive strength and flexural strength concrete. The compressive strength of the concrete increases as much as 21.21%, flexural strength of the concrete increases as much as 3.48%. Keywords: concrete, dry dust collector waste, compressive strength, flexural strength